Municipal plan of adaptation to climate change of Santa Rita 2019 - 2023 (Copan, Honduras) - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
This plan, elaborated in the ResCa bilateral project of CCAFS, defined the strategic action to enhance adaptation to the climate change capacity of the municipality of Santa Rita (Copan, Honduras).